Analisis Pengaruh Pertumbuhan Ekonomi, Angka Harapan Hidup, Tingkat Partisipasi Angkatan Kerja, dan Tingkat Pengangguran Terbuka Terhadap Tingkat Kemiskinan di Kota Surabaya, Kota Malang, Kota Madiun, Kota Pasuruan, dan Kota Batu - Almirah Luthfiyah Nur Aurellia; Marseto; Anisa Fitria Utami (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the influence of economic growth, life expectancy, labor force participation rate, and open poverty rate on poverty rate in five cities in East Java Province, namely Surabaya City, Malang City, Madiun City, Pasuruan City, and Batu City during the period 2013 to 2023. The method used is a quantitative approach with panel data regression analysis, which allows a combination of time series and cross-section data to obtain more accurate estimates. The main focus of this study is to identify how much each independent variable contributes to changes in poverty rates in the region. The results of this study are expected to be the basis for consideration in formulating poverty alleviation policies by local governments and to be an academic reference in the Faculty of Economics and Business UPN "Veteran" East Java. By understanding the factors that influence poverty empirically, it is hoped that regional development strategies can be directed more effectively and on target.